SUPERLATIVE FORMS OF ADJECTIVES BY ARTICLE NA + PREFIX UM- IN TOBA BATAK - Ambarita , Esron (Pascasarjana Universitas HKBP Nommensen, 2021)
The objectives of this study are to investigate the formation of superlative forms of adjectives by article na + prefix [um-] in Toba Batak. The results show that superlative forms of adjectives by article na + prefix [um-] in Toba Batak result in various morphological and phonological processes as follows: (1) if article na +prefix [um-] is attached to adjectives preceded by vowels [a], [e], [i], [o], and [u] the last phoneme of prefix [um-] is doubled i.e [um-] is pronounced as [umm-] sound. (2) if the initial phoneme is a bilabial plosive voiced consonant [b], prefix [um-] is pronounced as [ub-]sound as its allomorph. (3) if the initial phoneme is a velar plosive voiced consonant [g], prefix [um-] is pronounced as [uŋ-] sound. (4) if the initial phoneme is a palato alveolar affricate voiced consonant [j] prefix [um-] is spelt as [un-] sound but pronounced as [uj-] sound. (5) if the initial phoneme is a bilabial nasal voiced consonant [m] prefix [um-] does not change. (6) if the initial phoneme is an alveolar nasal voiced consonant [n], prefix [um-] is spelt and pronounced as [un-] sound. (7) if the initial phoneme is a bilabial plosive voiceless consonant [p], prefix [um-] is spelt as [um-] sound but pronounced as [up-] sound. (8) if the initial phoneme is an alveolar rolled voiced consonant [r], prefix [um-] is spelt and pronounced as [ur-] sound. (9) if the initial phoneme is an alveolar fricative voiceless consonant [s], prefix [um-] is spelt as [un-] sound but pronounced as [us-] sound. (10) if the initial phoneme is an alveolar plosive voiceless consonant [t], prefix [um-] is spelt as [un-] sound but pronounced as [ut-] sound.